(untitled) (Research, Society and Development, 2021)
Inclusive education has been constituted as an advance in the training of students with special educational needs, differentiating from the segregated model. In Pará, it has developed in regular education with specialized support, in addition to specific institutions. In Breves, in Marajó, activities in this perspective began in the 1980s, through training courses, a gradual and exclusive process, where participation was restricted only to those considered able to develop skills and competence in classes of regular education. In this sense, the objective was to know the current conjuncture of inclusive education in secondary education in the urban state network of Breves. The methodology corresponded to the application of questionnaires with semi-structured interviews to employees of the schools targeted by this study. The results are the constitution and discussion of the school history profiles; Inclusive school education; Profile of students PwD’s and the Profile of school accessibility. The need for pedagogical and structural accessibility in schools is conclusive, where inclusion is not limited to specialized educational services and accessible spaces, but an approach that promotes holistic inclusion, from institutional documents to pedagogical and social practices.